Literasi Parenting Sebagai Upaya Meningkatkan Indeks Pembangunan Literasi Masyarakat Kota Blitar - Suyatno, Suyatno; Askafi, Eka; Heru Widodo, Mochammad (Universitas Islam Kadiri, 2025)
Literacy i.e. reading and writing skills as well as thinking skills using sources of knowledge in print, visual, digital and auditorium forms. Literate society becomes a most solid social foundation to drive the process of transformation of society towards a peaceful life as well as to realize Indonesian society that has a cosmopolitan character in culture. The library is taking responsible for building the library and reading enthusiasm to create a community of learners and for building, developing and managing libraries, one of which is to improve literacy to realize a society of lifelong learners. The City Library and Archives Service of Blitar has a programme of work to cultivate the interest of the public in reading is parenting literacy. The objective of this qualitative analysis is to conduct SWOT analysis of the programme of activities to formulate recommendations for the strategy of optimizing the program of parenting literacy. The results of the research show that a strategy that can be described as Parenting Literacy Optimization being in Quadrant I which is favourable situation in optimizing opportunities and strengths that is aggressive policy-making (growth).